2018
DOI: 10.3892/etm.2018.7079
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of Houttuynia eye drops combined with olopatadine hydrochloride eye drops on vernal keratoconjunctivitis

Abstract: Therapeutic effects and safety of houttuynia eye drops combined with olopatadine hydrochloride eye drops on vernal keratoconjunctivitis (VK) were evaluated. A total of 926 patients with VK were collected in the Eye Hospital of Wenzhou Medical University from July 2011 to January 2017. Patients were divided into group A, B and C according to the use of different eye drops. Group A included 276 patients who were treated with houttuynia eye drops; group B included 305 patients who were treated with olopatadine hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Low potency steroids were prescribed in very early grades of VKC Medium Fiorentini and Khurram [ 122 ] 2019 United Arab Emirates 10 N/A To evaluate the use of topical 0.03% tacrolimus ointment for VKC in the Middle East 4 weeks of tacrolimus therapy permitted a significant reduction in signs and symptoms, without side effects Low Samyukta et al [ 123 ] 2019 India 30 8.2 To evaluate the efficacy of topical tacrolimus 0.03% monotherapy for the treatment of VKC After 8 months of treatment with tacrolimus 0.03%, VKC signs and symptoms fell drastically ( p < 0.001), with also an improvement in visual acuity ( p = 0.04) Medium Shoji et al [ 124 ] 2019 Japan 1821 19.3 To evaluate the efficacy of topical 0.1% tacrolimus ophthalmic suspension in chronic allergic conjunctival disease with and without atopic dermatitis Tacrolimus therapy decreased ocular signs and symptoms in both groups ( p < 0.0001). The concomitant use of topical steroids significantly increased the likelihood of remission ( p < 0.0001) Medium Xu and Cai [ 125 ] 2019 China 926 15.1 To evaluate therapeutic effects and safety of houttuynia eye drops combined with olopatadine hydrochloride eye drops on VKC A combination of houttuynia eye drops and olopatadine permitted a reduction in VKC symptoms ( p < 0.05), without side effects Low Modugno et al [ 126 ] 2020 Italy 23 18.4 To compare corneal morphologic changes in VKC patients treated with topical cyclosporine Cyclosporine therapy caused corneal mic...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low potency steroids were prescribed in very early grades of VKC Medium Fiorentini and Khurram [ 122 ] 2019 United Arab Emirates 10 N/A To evaluate the use of topical 0.03% tacrolimus ointment for VKC in the Middle East 4 weeks of tacrolimus therapy permitted a significant reduction in signs and symptoms, without side effects Low Samyukta et al [ 123 ] 2019 India 30 8.2 To evaluate the efficacy of topical tacrolimus 0.03% monotherapy for the treatment of VKC After 8 months of treatment with tacrolimus 0.03%, VKC signs and symptoms fell drastically ( p < 0.001), with also an improvement in visual acuity ( p = 0.04) Medium Shoji et al [ 124 ] 2019 Japan 1821 19.3 To evaluate the efficacy of topical 0.1% tacrolimus ophthalmic suspension in chronic allergic conjunctival disease with and without atopic dermatitis Tacrolimus therapy decreased ocular signs and symptoms in both groups ( p < 0.0001). The concomitant use of topical steroids significantly increased the likelihood of remission ( p < 0.0001) Medium Xu and Cai [ 125 ] 2019 China 926 15.1 To evaluate therapeutic effects and safety of houttuynia eye drops combined with olopatadine hydrochloride eye drops on VKC A combination of houttuynia eye drops and olopatadine permitted a reduction in VKC symptoms ( p < 0.05), without side effects Low Modugno et al [ 126 ] 2020 Italy 23 18.4 To compare corneal morphologic changes in VKC patients treated with topical cyclosporine Cyclosporine therapy caused corneal mic...…”
Section: Resultsmentioning
confidence: 99%
“…The last year, a large cohort study by Xu and Cai [ 125 ] aimed to evaluate the therapeutic effects and safety of houttuynia eye drops combined with olopatadine hydrochloride in VKC patients. They observed that children treated with the association of houttuynia and olopatadine eye drops showed a rapid reduction in VKC symptoms ( p < 0.05), without adverse effects.…”
Section: Therapymentioning
confidence: 99%
“…H. cordata also shows potential in combination with other drugs. As a traditional basic antiviral and antibacterial Chinese medicine, research on H. cordata eye drops combined with olopatadine hydrochloride in the treatment of vernal keratoconjunctivitis revealed the synergistic effect of this combination ( Xu and Cai, 2019 ). Additionally, a clinical trial involving mangosteen , Lithospermum officinale , Tribulus terrestris L., and H. cordata extracts in the treatment of mild to moderate acne showed that inflammation and noninflammatory skin lesion counts were significantly reduced ( Yang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…[12,1517] It is reported that Houttuynia eye drops (HED) can achieve good effect in the treatment of VKC. [18] However, there is no systemic review and meta-analysis published regarding the clinical efficacy of HED. Here we plan to run a systemic review and meta-analysis of randomized controlled trials (RCTs) to assess the efficacy of HED for the treatment of VKC.…”
Section: Introductionmentioning
confidence: 99%